PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE CARD SORT PADA SISWA KELAS III MIS AL WASHLIYAH BANDAR DURIAN - Ritonga, Sri Wahyuni (Jurnal Al-Fatih, 2024)
This study aims to improve the mathematics learning outcomes of third-grade students at MIS Al Washliyah Bandar Durian through the implementation of the cooperative learning method Card Sort using picture media. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 14 third-grade students. Data were collected through observation, learning outcome tests, and documentation. The results showed that the application of the Card Sort method significantly improved students’ learning outcomes. In the pre-cycle stage, the percentage of mastery learning was only 28.57%, which increased to 64.29% in cycle I and reached 92.86% in cycle II. This improvement indicates that learning through the Card Sort method made students more active, motivated, and better able to understand the concept of arithmetic operations through the activity of sorting picture cards. Therefore, it can be concluded that the Card Sort method with picture media is effective in improving mathematics learning outcomes for elementary school students.